Volunteer use and non-use values, satisfaction and future engagement in a sport event - Mahadevan, Renuka (Event Management, 2020)
This study examines the influence of use and non-use values on volunteers’ satisfaction and their continued future engagement in a sports event. Using the case study of the Arctic Winter Games, evidence showed that non-use values have a higher impact on satisfaction but use values outweigh non-use values’ direct influence on the intention to volunteer again due to the strong mediating effect of satisfaction in the effect of non-use values on intention to volunteer again. Some of these effects were significantly different based on gender, first-time volunteers and the younger generation. Both use and non-use values had greater impact on satisfaction for the indigenous than non-indigenous group. The results point to the new potential for using use and non-use values to target different groups to continue volunteering.